THE EFFECT OF LEVERAGE, EARNINGS PER SHARE, AND DIVIDEND POLICY ON COMPANY VALUE - Maulidina, Fais Indriani; Paramita, Ratna Wijayanti Daniar; Taufiq, Muchamad (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
This study aims to determine the effect of leverage, earnings per share, and dividend policy on firm value in manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. This study uses a quantitative approach method. The population in this study were 182 companies. sampling technique using purposive sampling method, in order to obtain 38 companies that meet the criteria for 2017-2019. The results of this study conclude that: 1) Leverage has no effect on firm value because the company uses more capital to fund its assets than debt. 2) Earnings per share does not affect the value of the company because the increase and decrease in earnings per share will not affect the value of the company, but is influenced by other factors. 3) Dividend policy has a significant effect on firm value because the higher the dividend policy, the more regular dividends will be distributed by the company, this will make investors interested in investing.